Manajemen Peserta Didik Dalam Meningkatkan Kedisiplinan Siswa di SMP Islam Al-Hijrah - Ilyas Rohili; Basuki; Haditsa Qur'ani Nurhakim (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
The purpose of this study was to find out more about how student management at Al-Hijrah Islamic Junior High School can help improve student discipline. This study used a qualitative methodology with a descriptive qualitative approach. The researcher used observation, interview, and documentation methods to collect data for this study. Data analysis began with data collection, reduction, storage, and verification. The researcher also used data triangulation methods to ensure that the data was correct. This study shows that student management at Al-Hijrah Islamic Junior High School includes planning, acceptance, grouping, attendance, training, class promotion, transfer, graduation, alumni, extracurricular activities, and services. To maintain student discipline, there are rules and regulations. Students who violate the rules or regulations will be assessed through a point weighting system. To improve student discipline, there are student guardian meetings, stamped work agreements, student grouping based on supervising teachers, student attendance lists, letters of reprimand or warning, letters of permission to leave lessons, and security guard permit cards. Students work together with the person in charge of each planned activity when doing it. Some of the services offered by the school include health services, library, guidance counseling, transportation, and canteen to help student management. Students must obey school rules to improve discipline. if students violate school rules, they will get points. Each violation is given different points, and students will be returned to others after getting 100 points.